Thermal and physical properties of (Choline chloride + urea + l-arginine) deep eutectic solvents - Chemat, F. (Elsevier B.V., 2016)
In the present work, a common amino acid, l-arginine (0.05, 0.10, 0.15 and 0.20 mol) was added to (Choline chloride + urea) to form ternary deep eutectic solvents. The thermal properties namely, melting point, glass transition temperature, thermal decomposition temperature, and molar heat capacity and the physical properties namely, density, viscosity (298.15-353.15) K and refractive index (298.15-333.15) K were measured. Addition of l-arginine increases the thermal stability, molar heat capacities and glass transition temperatures of the eutectic solvents, and on the other hand it reduces the thermal expansion coefficients. The physical properties namely, density, viscosity and refractive index were also found to increase with increasing molar ratio of l-arginine. The physical properties were correlated as a function of temperature to represent the present data. Â© 2016 Elsevier B.V. All rights reserved.